Penerapan Teknik Elektrokoagulasi dalam Pengurangan Bahan Organik Air Limbah Kegiatan Perikanan - Fitri Afina Radityani; Sigid Hariyadi; Suprihatin Suprihatin; Dede Heri Yuli Yanto; Sita Heris Anita (Institut Pertanian Bogor, 2020)
Electrocoagulation is one of physical techniques in waste-water treatment that applicable for organic waste from aquaculture. This research aims to determining the effectivity of electro-coagulation technique with different electrical voltages and duration consumed in waste-water treatment. The treatments used two electrical voltage levels (6 dan 12V) and four different durations of time consumed (15, 30, 45, and 60 minutes). The result showed the changes of water quality. Decreasing values shown by Chemical Oxygen Demand (COD) at the voltage of 12V and duration of 60’ (in about 82,89%); orthophosphate at the voltage of 12V and duration of 45’ (67.49%); turbidity at the voltage of 12V and duration of 60’ (69.65%); color at the voltage of 12V and duration of 60’ (70.49%); Total Suspended Solid (TSS) at the voltage of 12V and duration of 15’ (31.90%); and Total Dissolved Solid (TDS) at the voltafe of 12V and duration of 60’ (10.31%). Furthermore, increasing values were found in parameters of free ammonia at the voltage of 12V and duration of 15’ (291.09%); ammonium at the viltyage of 12V and duration of 30’ (8.85%); and pH at the voltage of 6V and duration of 60’ (16%). The best treatment in improving water quality of treated organic waste from aquaculture was the voltage of 12V for 30 minutes. Keywords: electro-coagulation, organic materials, water quality, waste-water treatment